2021
DOI: 10.1071/an21422
|View full text |Cite
|
Sign up to set email alerts
|

Can a return to small ruminants increase profitability and drought resilience in the semiarid rangelands of northern Australia?

Abstract: Context. The semiarid rangelands of northern Australia have high climate variability and a history of suffering periodic severe droughts. To remain viable, livestock businesses in the rangelands need to build resilience to climatic and market variability by regularly producing a profit and increasing wealth. Aims. Our aim was to use the farm-management economics framework to conduct a contemporary assessment of the profitability and resilience of alternative livestock enterprises in the semiarid rangelands of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…This financial risk is challenging for property managers where high costs of wild dog exclusion fencing must be funded wholly by the property. Similar results were obtained for conversion from beef to goat production for a representative property in the central-western rangelands of Queensland (Bowen and Chudleigh 2021d).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…This financial risk is challenging for property managers where high costs of wild dog exclusion fencing must be funded wholly by the property. Similar results were obtained for conversion from beef to goat production for a representative property in the central-western rangelands of Queensland (Bowen and Chudleigh 2021d).…”
Section: Discussionsupporting
confidence: 75%
“…Carbon farming and rangeland goat production provide a diversified income for a beef property, potentially stabilising income over time as well as improving average profitability. This can reduce risks from climate variability and assist with drought preparedness and resilience (Buxton and Smith 1996;Freebairn 2019;Bowen and Chudleigh 2021d). However, as identified previously Chudleigh 2021a, 2021b), individual properties may have characteristics different from those assumed in this analysis.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“… Fordyce et al., (2021) defined the primary business measure of liveweight production for beef cows in northern Australia and reported that liveweight production in breeding beef cows was primarily governed by available nutrition and mating outcome. Bowen & Chudleigh (2021b) utilised a farm-management economics framework to conduct a contemporary assessment of the profitability and resilience of alternative livestock enterprises in the semiarid rangelands of northern Australia. They reported that meat sheep and rangeland meat goat enterprises produced the greatest rate of return on total capital where existing small ruminant enterprises in the semiarid rangelands of Queensland were profitable and resilient alternatives.…”
Section: Introductionmentioning
confidence: 99%